(untitled) (American Journal of Islam and Society, 2015)
Slavery, the State, and Islam is Fagan’s English rendering of Mohammed Ennaji’s 2007 work Le Sujet et le Mamelouk: Esclavage, Pouvoir et Religion dans le Monde Arab, a historical study of the economics of power in the relationship among slavery, Islam, and monarchy. Ennaji investigates the structure and nature of the “bond of authority” as it manifests itself in servitude between the king and subject, master and slave, God and believers. The bulk of his primary historical material belongs to the first few centuries of Islam. However his intention, as he notes in the introduction, is to also make sense of contemporary modes of power that govern the scene of authority in the individuals’ proximity to the state and, in some instances, to one another. The opening chapter tells an anecdote of a nineteenth-century Moroccan official who was stripped of his title as Local Governor (in Arabic, Qaid), declared dead to the public, and kept as a slave in the sultan’s palace. Ennaji challenges the official narrative and weaves novel threads of the story to show the degree to which the bond of authority between the sultan and his servants depends upon uninterrupted flat obedience. The second chapter questions the issue of slavery during Islam’s early years. The author claims that the new religion made little practical changes to this institution and, in certain cases, made slaves even more abjectly submissive to their masters. Ennaji particularly details Islam’s termination of the statuses of sa’b (a sā’ib is a slave who has attained full unconditional freedom) and ṭalq (repudiation) and its admission of mawlā (freed slaves must remain loyal to their ex-master). He also elaborates on the non-provision of part of the public funds to free more slaves, as well as the practice of depriving freed slaves of the spoils of war and discouraging people from marrying them. In the third chapter, Ennaji undertakes the king-subject relation in light of the notion of servitude. He probes the sociolinguistic roots of several conceptualizations, including ‘ibādah, ra’īyah, and ṭā‘ah (translated successively as adoration, people, and obedience). He also examines the semiotics of various expressions of servitude and presents a prolonged discussion of the different uses of the hand in this context. Ennaji contends that the transition to Islam barely changed anything in the structure of authority and the masterslave relationship. As he puts it, with the advent of Islam there was “a reorganization of the authoritarian space that reshuffled the division of power between the king and the divine authority” (p. 82). This redistribution of power is elaborated in the fourth chapter, where the author draws on concepts used ...